The Role of Information Technology in Governance Mechanism for Strategic Business Contribution: A Pilot Study - Setyadi, Resad; Abd Rahman, Aedah; Subiyakto, A'ang (Society of Visual Informatics, 2023)
Information Technology Governance (ITG) aligns IT and business transformation in schools. Private schools need to implement a method to evaluate the process of aligning IT strategy with business strategy and whether IT investment supports business objectives. Â What factors influence the ITG of selected Indonesia High School (HS) aligning IT-Business strategy? Partial Least Squares Structural Equation Modeling (PLS-SEM) is a tool for analyzing the ITG model results in this study. The result is the composition of 9 variables with four independent variables (as structure mechanism variables), four dependent variables (as process and relational mechanism variables), and the ITG variable (as the final variable) shows a significant value of 0.75 at the ITG variable. This considerable value means that the ITG supporting variables of four independent and four dependent variables significantly affect the ITG variable by 75%. This study provides information if the system trust variable is increasing due to the influence of good IT strategy (independent) variables and good business (dependent) variables. The recommendation is that this ITG trust model can be used to evaluate the alignment of IT strategy with business strategy and whether IT investment supports business objectives in HS